LECTURE ABSENTEEISM IN ALGERIAN HIGHER EDUCATION: A CONCEPTUAL FRAMEWORK FOR MULTI-LEVEL ANALYSIS IN THE POST-PANDEMIC ERA (2020–2024) - Benziane Djamel, (International Journal of Innovative Technologies in Social Science, 2025)
Chronic lecture absenteeism has emerged as a persistent challenge in Algerian higher education, particularly after the COVID-19 pandemic. This theoretical article synthesizes the scholarship to construct an integrated, multilevel framework for understanding the drivers of non-attendance. Moving beyond an individual deficit view, it posits that attendance decisions result from interactions across five nested systems: the micro-system of the student's immediate environment, the meso-system of connections between micro-level components, the exo-system of broader institutional structures, the macro-system of societal forces, and the chrono-system of temporal influences. Key factors include the uneven digitalization of learning systems, linguistic friction in instruction, assessment misalignments, and labor market signals. The analysis shows that the shift to distance learning has devalued physical presence for many students, while exposing disparities in digital access and academic literacy. Consequently, a pattern of disengagement has emerged, characterized by minimizing strategic efforts and a weakened scholarly identity. To counter these trends, this study presents multilevel intervention propositions, emphasizing the need to restore attendance value through participatory pedagogy, formative assessment, and quality assurance mechanisms. It argues for a systemic approach addressing micro-level behavioral norms, meso-level instructional designs, exo-level institutional processes, and macro-level policy frameworks. The article concludes with a call for empirical testing of these propositions to guide evidence-based reforms.